Association between the Effectiveness and Adequacy of Patient Education among Patients with Chronic Renal Disease - Alhajjaj Yousef Althagafi , Hanaa Ayadah Alasslani , Salem Naji Alharbi , Ahmed Dakhilallah M Alluqmani , Muhannad Abdulhamid Sanari , Abdallah Faisal Alharbi; Ahmad Adnan Alharbi , Mohammed Abdulmohsen Al Luhaybi , Mohammed abdulqader janbi , Hatim Meshal Almatrafi , Fahad Fadhi A Alharbi (Migration Letters, 2022)
Background: Renal disease is an important public health problem. Patient education improves health and treatment adherence of patients with chronic renal disease. However, evidence about the sufficiency of patients’ knowledge processed in patient education is limited. The study aims: to analyze the relationship between the sufficiency and usefulness of patient education among patients with chronic renal disease. Also, aims to discover whether both sufficiency and usefulness need to be analyzed in the quality evaluation of patient education. Methods: A descriptive cross-sectional study was conducted in the dialysis units of two hospitals in Makkah, KSA from January to March 2022. Patients undergoing pre-dialysis or hemodialysis care (N = 162) evaluated both the sufficiency and usefulness of patient education provided by nephrology nurses by using parallel structured questionnaires. Results: A strong relationship was found between the sufficiency and usefulness of patient education. The relationship was significant across all dimensions of empowering knowledge, but no systematic association was found between the sufficiency-usefulness relationship and background variables. Conclusion: Depending on the purpose of evaluating patient education, either aspect, that is, sufficiency or usefulness can be used, but it is not necessary to use both due to their strong inter-correlation. In terms of implications for practice, consideration of both sufficiency and usefulness is important when providing empowering patient education for people undergoing pre-dialysis or hemodialysis, but only one aspect needs to be evaluated.